2011
DOI: 10.1016/j.dental.2011.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The use of sodium trimetaphosphate as a biomimetic analog of matrix phosphoproteins for remineralization of artificial caries-like dentin

Abstract: Objectives-This study examined the use of sodium trimetaphosphate (STMP) as a biomimetic analog of matrix phosphoproteins for remineralization of artificial carious-affected dentin.Methods-Artificial carious lesions with lesion depths of 300±30 µm were created by pHcycling. 2.5% hydrolyzed STMP was applied to the artificial carious lesions to phosphorylate the partially-demineralized collagen matrix. Half of the STMP-treated specimens were bonded with One-Step. The adhesive and non-adhesive infiltrated specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 55 publications
1
102
0
3
Order By: Relevance
“…The infiltration of hydrophilic resin monomers into demineralized collagen matrix, to produce a hybrid layer (HL) that couples adhesives/ resin composites to the underlying mineralized dentine, provides ample opportunity for nano-leakage to occur beneath the restoration: oral fluids penetrate any poorly infiltrated area and serve as functional medium for the functioning of host-derived, collagen degrading matrix metalloproteinases (MMPs) 3) . While each experimental strategy that attempted to overcome these problems has its own benefits and reciprocal limitations 4) , progressive water replacement by hydroxyapatite generated during dentine remineralization may be a suitable strategy for extending the service life of resin-based dentine bonding procedures and its actualization has been a source of conjecture until now 5) . In this case, nano-leakage might only be a temporary phenomenon that could be solved by new hard-tissue formation 6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infiltration of hydrophilic resin monomers into demineralized collagen matrix, to produce a hybrid layer (HL) that couples adhesives/ resin composites to the underlying mineralized dentine, provides ample opportunity for nano-leakage to occur beneath the restoration: oral fluids penetrate any poorly infiltrated area and serve as functional medium for the functioning of host-derived, collagen degrading matrix metalloproteinases (MMPs) 3) . While each experimental strategy that attempted to overcome these problems has its own benefits and reciprocal limitations 4) , progressive water replacement by hydroxyapatite generated during dentine remineralization may be a suitable strategy for extending the service life of resin-based dentine bonding procedures and its actualization has been a source of conjecture until now 5) . In this case, nano-leakage might only be a temporary phenomenon that could be solved by new hard-tissue formation 6) .…”
Section: Introductionmentioning
confidence: 99%
“…As remineralization proceeds, free and loosely bound water becomes less readily available to MMPs to initiate autolytic phenomena. Moreover, catalytic and allosteric domains of these enzymes may be fossilized and inactivated by the deposition of hydroxyapatite crystallites between polymer matrices and exposed collagen fibrils 5) . It has been suggested that molecular immobilization of the functional activity of collagenolytic enzymes could be accomplished in dental restorations with a guided tissue approach 7) .…”
Section: Introductionmentioning
confidence: 99%
“…If TMP thereby replaced dissolved phosphate groups, the stronger adsorbing TMP groups would protect the surface against dissolution during a subsequent caries attack [McGaughey and Stowell, 1977]. Recently, a renewed interest in TMP has been shown for its role as a biomimetic analog of matrix phosphoproteins in the enhancement of carious dentine remineralization [Liu et al, 2011].…”
mentioning
confidence: 99%
“…This strategy reproduced both intrafibrillar and interfibrillar minerals and recapitulated the dimension and order of the apatite crystallites that are found in natural dentin [70][71][72][73]. Using this biomimetic remineralization strategy, both hybrid layers created by etch-and-rinse adhesives [68,74,75] and moderately aggressive self-etch adhesives [65,74,76], as well as 250-to 300-μm-thick completely demineralized dentin lesions, can be remineralized [77][78][79]. This bottom-up remineralization strategy does not rely on seed crystallites, and may be considered as a potentially useful mechanism in extending the longevity of resin-dentin bonds [80] via restoring the dynamic mechanical properties of the denuded collagen within the hybrid layer to approximate those of mineralized dentin [81].…”
Section: Fluoride-free Adhesivesmentioning
confidence: 99%